Conformational disorder in energy transfer: beyond Förster theory - Nelson, Tammie (2013)
Energy transfer in donor–acceptor chromophore pairs, where the absorption of each species is well separated while donor emission and acceptor absorption overlap, can be understood through a Förster resonance energy transfer model. The picture is more complex for organic conjugated polymers, where the total absorption spectrum can be described as a sum of the individual contributions from each subunit (chromophore), whose absorption is not well separated. Although excitations in these systems tend to be well localized, traditional donors and acceptors cannot be defined and energy transfer can occur through various pathways where each subunit (chromophore) is capable of playing either role. In addition, fast torsional motions between individual monomers can break conjugation and lead to reordering of excited state energy levels. Fast torsional fluctuations occur on the same timescale as electronic transitions leading to multiple trivial unavoided crossings between excited states during dynamics. We use the non-adiabatic excited state molecular dynamics (NA-ESMD) approach to simulate energy transfer between two poly-phenylene vinylene (PPV) oligomers composed of 3-rings and 4-rings, respectively, separated by varying distances. The change in the spatial localization of the transient electronic transition density, initially localized on the donors, is used to determine the transfer rate. Our analysis shows that evolution of the intramolecular transition density can be decomposed into contributions from multiple transfer pathways. Here we present a detailed analysis of ensemble dynamics as well as a few representative trajectories which demonstrate the intertwined role of electronic and conformational processes. Our study reveals the complex nature of energy transfer in organic conjugated polymer systems and emphasizes the caution that must be taken in performing such an analysis when a single simple unidirectional pathway is unlikely.